CCAFS Knowledge and Evidence Inform World Bank Group (WBG) Investments in Agricultural Development - Kristjanson, Patricia M. (2019)
Three years ago, a strategic decision was made to embed a CCAFS researcher within the agriculture group at WBG headquarters. The underlying reasoning behind this approach, i.e. the theory of change, was a belief that if WBG-supported agriculture projects, analytical tools, and knowledge products are designed using the most recent applied research knowledge about Climate-Smart Agricultural (CSA) opportunities, including about Climate Change (mitigation and adaptation) cobenefits, it will increase the breadth and depth of the impacts of these investments. The World Bank is a leading financier of agricultural development projects globally, with investments worth $6.8 billion in 2018, reaching over 30 low-income countries, among others. Thus enhancing the effectiveness of these investments will have considerable impacts globally.